2013
DOI: 10.1101/gad.217240.113
|View full text |Cite
|
Sign up to set email alerts
|

The methyltransferase SMYD3 mediates the recruitment of transcriptional cofactors at the myostatin and c-Met genes and regulates skeletal muscle atrophy

Abstract: Elucidating the epigenetic mechanisms underlying muscle mass determination and skeletal muscle wasting holds the potential of identifying molecular pathways that constitute possible drug targets. Here, we report that the methyltransferase SMYD3 modulates myostatin and c-Met transcription in primary skeletal muscle cells and C2C12 myogenic cells. SMYD3 targets the myostatin and c-Met genes and participates in the recruitment of the bromodomain protein BRD4 to their regulatory regions through protein-protein int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 77 publications
4
75
0
1
Order By: Relevance
“…Treating rats with the glucocorticoid receptor antagonist RU486 prevented this increase in myostatin expression 66 . A similar increase in myostatin mRNA levels was also observed after dexamethasone treatment in cultured myotubes 120,121 and in the muscles of mice 122 . Although glucocorticoid receptor antagonists or adrenalectomy can prevent muscle wasting in models of fasting and cancer, other studies found no beneficial effect of these drugs on muscle wasting following burn injury 123 or uraemia 124 , and the loss of adrenal steroids and their many protective functions was deleterious to the stressed individual.…”
Section: Muscle Atrophy During Systemic Diseasesupporting
confidence: 72%
“…Treating rats with the glucocorticoid receptor antagonist RU486 prevented this increase in myostatin expression 66 . A similar increase in myostatin mRNA levels was also observed after dexamethasone treatment in cultured myotubes 120,121 and in the muscles of mice 122 . Although glucocorticoid receptor antagonists or adrenalectomy can prevent muscle wasting in models of fasting and cancer, other studies found no beneficial effect of these drugs on muscle wasting following burn injury 123 or uraemia 124 , and the loss of adrenal steroids and their many protective functions was deleterious to the stressed individual.…”
Section: Muscle Atrophy During Systemic Diseasesupporting
confidence: 72%
“…BETi exhibit broad transcriptional effects by targeting the general transcriptional elongation factor p-TEFb's interplay with Brd4. It is possible that systemic features of cancer such as inflammation (46) and muscle wasting by glucocorticosteroid treatment (47), known to be mediated by transcriptional elongation, could be targeted by BETi too for the benefit of cancer patients. Importantly, however, early trials will have to determine whether a combination treatment using BETi and HDACi will be tolerated in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…DNA binding to the N-lobe has been shown to enhance SMYD3 methyltransferase activity [18]. The interaction of SMYD3 with BRD4 mediates the recruitment of transcriptional cofactors at the myostatin gene and regulates skeletal muscle atrophy [8]. SMYD3 interacts with PC4 in tumor cells and such interaction stimulates oncogenic gene expression through deposition of H3K4 tri-methylation [7].…”
Section: Discussionmentioning
confidence: 99%